Cholesterol-Lowering Drugs on Akt Signaling for Prevention of Tumorigenesis - Kumar, Navneet; Mandal, Chandi C. (Frontiers in Genetics, 2021)
Cholesterol has been reported to be accumulated in cancer cells. The metabolic dysregulation of the cholesterol is associated with tumor development and progression. The cholesterol-lowering drugs have been found to be involved in the prevention and treatment of various cancers. Akt, a serine/threonine kinase, can modulate the role of several downstream proteins involved in cell proliferation, migration, invasion, metabolism, and apoptosis. Since its involvement in several signaling pathways, its dysregulation is commonly reported in several cancers. Thus, targeting Akt could be an effective approach for cancer prevention and therapy. Cholesterol-lowering drugs have been found to affect the expression of Akt, and its activation in the cancer cells and thus have shown anticancer activity in different type of cancers. These drugs act on various signaling pathways such as PTEN/Akt, PI3k/Akt, Akt/NF-κB, Akt/FOXO1, Akt/mTOR, etc., which will be discussed in this article. This review article will discuss the significance of cholesterol in cancer cells, cholesterol-lowering drugs, the role of Akt in cancer cells, and the effects of cholesterol-lowering drugs on Akt in the prevention of therapy resistance and metastasis.